How to lead a values-based professional services firm : 3 keys to unlock purpose and profit - Scales, Don; Biderman-Gross, Fran (John Wiley & Sons, Inc., 2020)
"Brand values -- the core attributes and beliefs of a company -- are the heart and soul of any professional services firm. Professional services firm that consistently deliver on their brand values, such as ad agency R/GA and consultancy Accenture, achieve spectacular growth. But all it takes is one misstep, and a services firm can collapse overnight as Arthur Andersen did. How to Manage a Values-Based Professional Services Firm shows leaders of professional services firms how to embed brand values in everything their firm does. The book argues that because professional services firms don't sell products, they are differentiated based on the ability of their leaders to cultivate a culture that engages and appreciates its teams and aligns with its markets. Therefore, the company's shared values shared must permeate everything the company does, ranging from hiring talent to managing client relationships, and even how they select and interact with vendors"--